Group Communication Support in Supporting the Resilience of Families and Survivors of Covid-19 - Rose emmaria Tarigan (Jurnal Komunikasi, 2021)
The Covid-19 pandemic originating from Wuhan has caused a lot of problems in people’s life aside from the economic costs. The Covid-19 has also taken its toll in almost every country in the world. Millions have died. Families need communication supports to face Covid-19. Group communication support has a very important role in sustaining the Covid-19 survivors and their families. To understand how it can sustain the Covid-19 survivors and their families, the researcher used the case-study approach and collected data through in-depth interviews with three respondents and analyzed them. This study aims to find out how the role of group communication support for survivors in supporting their resilience against Covid-19. The result shows that group communication supports link with five skills in designing supportive messages, i.e.: clarifying supportive intentions, buffering face threats, using other-centered messages, framing messages, and giving advice. These five skills provide a positive influence to the survivors and their families. The support messages have helped them go through difficult times caused by Covid-19. The research also found other sustaining aspects: the ability of the three respondents to see the calamities positively according to their religions and their strong personalities. Their personalities have enabled them to show positive attitudes to their children. In turn, their children also have the same resolute, strong, and resilient attitude in facing their calamities. Pandemi Covid-19 yang berasal dari Wuhan, telah menimbulkan banyak masalah bagi kehidupan manusia, tidak hanya kerugian secara ekonomi saja. Covid-19 juga telah merenggut banyak nyawa manusia hampir di semua belahan dunia. Jutaan nyawa melayang dan jutaan keluarga membutuhkan adanya dukungan komunikasi sebagai akibat serangan Covid-19 ini. Dukungan komunikasi kelompok memiliki peranan yang sangat penting guna menunjang ketahanan dari keluarga dan juga penyintas Covid-19 ini. Untuk mengetahui bagaimana dukungan komunikasi kelompok bisa menunjang ketahanan keluarga dan penyintas Covid-19, maka dilakukan penelitian dengan pendekatan studi kasus, yakni mengumpulkan data melalui wawancara mendalam kepada tiga informan dan selanjutnya menganalisisnya. Penelitian ini bertujuan untuk menemukan bagaimana peranan dukungan komunikasi kelompok terhadap penyintas dalam menunjang ketahanan mereka menghadapi Covid-19. Hasil penelitian ini menunjukkan bahwa, dukungan komunikasi dari kelompok terkait dengan lima kemampuan mengemas pesan yang mendukung (support message), antara lain; clarify supportive intentions, buffering face threats, other centered message, framing, giving advice. Kelima keterampilan ini memberi pengaruh yang positif, kepada keluarga dan korban Covid-19. Adanya support message ini, membuat keluarga dan penyintas Covid-19 mampu melewati masa sulit sebagai akibat dari Covid-19 ini. Penelitian ini juga menemukan, bahwa terdapat aspek lainnya yakni, kemampuan yang dimiliki ketiga informan untuk melihat musibah yang mereka alami secara positif sesuai dengan ajaran agama yang mereka yakini, dan juga kekuatan kepribadian mereka yang tangguh. Kepribadian yang kuat, yang mereka miliki membuat mereka berhasil menunjukkan sikap positif kepada anak-anak mereka. Sebagai akibatnya, anak-anak merekapun memiliki sikap yang sama yakni tegar, kuat, tabah menjalani musibah yang mereka alami.